2013
DOI: 10.1007/s11882-013-0391-7
|View full text |Cite
|
Sign up to set email alerts
|

Food Allergy and Quality of Life: What Have We Learned?

Abstract: Health-related quality of life (HRQL) has become an emerging focus of interest in food allergy. Food allergy is a disease characterized by low mortality and symptoms which only occur during an allergic reaction. However, food-allergic patients continuously need to be alert when eating in order to prevent potentially severe allergic reactions, which may be fatal. Fear of such reactions and the need to be continuously vigilant may seriously compromise their HRQL. During the last decade, numerous studies have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…In the last decade, there has been a growing interest in the development of questionnaires to measure the impact of food allergy (DunnGalvin et al 2015). Previous qualitative and quantitative research on food allergy in families has typically involved mothers as caregivers (Akeson et al 2007, van der Velde et al 2013, Stjerna et al 2014, Knibb et al 2016, Warren et al 2016. Only two studies were found involving fathersone in which mothers reported higher impact on quality of life and greater anxiety and stress than fathers (King et al 2009), and another in which mothers reported reduced quality of life but greater empowerment compared to fathers (Warren et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, there has been a growing interest in the development of questionnaires to measure the impact of food allergy (DunnGalvin et al 2015). Previous qualitative and quantitative research on food allergy in families has typically involved mothers as caregivers (Akeson et al 2007, van der Velde et al 2013, Stjerna et al 2014, Knibb et al 2016, Warren et al 2016. Only two studies were found involving fathersone in which mothers reported higher impact on quality of life and greater anxiety and stress than fathers (King et al 2009), and another in which mothers reported reduced quality of life but greater empowerment compared to fathers (Warren et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Research into quality of life and related metrics have become more prevalent for FIA, including in the adolescent realm (Flokstra-de Blok et al, 2008;Resnick et al, 2010;van der Velde et al, 2009). Although allergy researchers have demonstrated a strong interest in quality of life (Valentine & Knibb, 2011;Van der Velde, Dubois, & Flokstra-De Blok, 2013) and the detrimental psychosocial effects of FIA (Cummings, Knibb, King, & Lucas, 2010), none of these research instruments can offer us in-depth, specific reasons why quality of life is lower in young people with allergy and their families. Instead, we must turn to research methods which focus on exploring individual situations.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, severe life-threatening reactions do occur. These are unpredictable, resulting in a perception of risk that adversely affects the healthrelated quality of life (HRQoL) to a degree comparable to chronic illnesses such as diabetes (6). Attempts to reduce this are hampered by our inability to identify those at greatest risk.…”
mentioning
confidence: 99%